Pengaruh Leverage Melalui Investment Opportunity Set terhadap Nilai Perusahaan pada Perusahaan Industri Pertanian di Bursa Efek Indonesia Periode 2018-2021 - Hardiyanti, Siti Dwi; Solikhin, Agus; Khalik, Idham (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to test and determine the effect of Leverage through Investment Opportunity Set on Company Values in the Agricultural Companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The analysis tool used in this study is SmartPLS Analysis. The result shows that the leverage variable has no significant and positive effect on the company values. It also has no significant and negative effect on Investment Opportunity Set. However, the Investment Opportunity Set variable has a significant and positive effect on company values. It is unable to mediate the effect of the leverage variable on the company value in the agricultural based-industries recorded in the Indonesia Stock Exchange for the 2018-2021 period